SIMULATION INTELLECTUAL SIGN #Aniespresiden2024 IN SOCIAL MEDIA BIGDATA ANALYSIS - Daherman, Yudi; Taufiq, Ivan (JWP (Jurnal Wacana Politik), 2024)
Talking about 2024 is of course talking about the political year in Indonesia. 2024 is the year when legislative candidates and of course presidential and vice presidential candidates will begin to fight. Currently, one of the presidential candidates from the party that is the current government party is Anies Baswedan. Based on what has been regulated in political ethics and election ethics, it is certainly not allowed to campaign by presidential candidates before the campaign period is carried out, but what happened was the emergence of social media content from Anies Baswedan containing campaigns with disguised signs and also camouflaged content so that what the public eye sees presented in cyberspace is only the content of his daily activities. This study aims to determine how Anies Baswedan’s political branding simulation in preparation for the 2024 Presidential Election. This research uses simulation analysis on Jean Baudrillarde’s theory based on big data analysis on Tiktok social media through content related to Anies’ candidacy as a 2024 Presidential candidate. The focus of the research is the arrangement and meaning of #aniesPresiden2024 signs and messages on mainstream social media received by the digital community and then forming a simulation of Anies Baswedan’s political branding which is the result of the digital communication process towards Anies’ political representation as a 2024 presidential candidate. The results of this study found that tiktok social media has a huge influence on the political branding of anies baswedan, digital society widely receives and consumes information related to the intellectual sign of anies baswedan.